[Ge12{FeCp(CO)2} 8 {FeCp(CO)}2]: a Ge12 core resembles the arrangement of the high-pressure modification Germanium (II) - Schenk, Christian; Henke, Florian; Schnepf, Andreas (Angewandte Chemie. International edition, 2013)
Similar yet different: The reaction of a GeBr solution with K[FeCp(CO)2] (Cp=η-C5H5) gives [Ge12FeCp(CO)28FeCp(CO)2] (1), whose oblong, highly cross-linked cluster core reveals a cut-out of the high-pressure solid-state structure of germanium (II) (see scheme). Mass spectrometric investigations on the gas-phase species [Ge6FeCp(CO)26FeCp(CO)]− (2) and theoretical calculations on 1 and 2 illuminate the formation of the metalloid cluster 1.